Animal Viral Disease Diagnostics - Dhama, K.; Shrivastava, Sameer; Rajak, Kaushal K.; Kumar, G.V.P.P.S. Ravi; Tiwari, Ashok K. (Indian Farming, 2015)
The IVRI has significantly contributed for diagnosis of animal diseases both in the pre-independence and post-independence era. Several nucleic acid based assays for detection and differentiation of imporant viral diseases, PCR, RT-PCR and real time PCR were developed for dignosis of bovine papallomia virus. Besides these, the scientists at the institute are also engaged in developing various serological tests and kits for detection of virus antibody/antigens. A continuous effort on the part of scientists is going on for improving animal disease diagnosis and undertaking research in frontier areas.